(untitled) (Research, Society and Development, 2021)
The theoretical essay aims to construct the variant nature idea, considering the concept of second nature as a major factor in this vein. For this purpose, the text was subdivided into four paragraphs. In the first one, a brief introduction is used, which aims to present the social landscape of residents domiciled in subnormal agglomerates. In the second paragraph, we seek to understand and reverberate the figuration of emotions self-control from the perspective of Eliasian procedural sociology. In the third, the theoretical perspective on the poor-black-slumdweller psychogenesis is emphasized. Finally, in the fourth paragraph, the need for (re)adaptation of slum groups are discussed. Briefly, the essay focuses on grounding a kind of social knowledge, distinctive from the poor-black-slumdweller population, resulting from the mutability and dynamics of interpersonal relationships, which, incorporated within the marginalized communities of Rio de Janeiro city, act to model a unique nature, variant. In other words, an extremely particular collective ego derivative from the imponderability of conflagrated subsistence.